ANALISIS KELUARGA BERISIKO STUNTING : HASIL PEMUTAKHIRAN PENDATAAN KELUARGA TAHUN 2022 DI KECAMATAN KETANGGUNGAN KABUPATEN BREBES - Sri Lestari, Sri Lestari; Wibowo, Hariyadi; Cahyono, Bambang Eko; Prasetya, Lalu Kekah Budi; Nafsi, Izatun; Sholihat, Siti Ilmawati (Jurnal Kesehatan, 2024)
Stunting is a nutritional challenge in Indonesia that is still unresolved and shows a high prevalence in Brebes Regency, which is 29,1%. Stunting prevention efforts must be pursued by optimizing the role of the family in the first 1000 days of life (1000 HPK), one of which is through the approach of families with stunting risk. This study is an analysis of families with stunting risk from the result of updating family data collection in 2021 in Ketanggungan district, Brebes Regency will be carried out in 2022. The aim of this research is to ascertain the risk elements and main risk factors that exist in families at risk of stunting in Ketanggungan District. This study uses a mixed method approach with descriptive analysis and cross sectional design. Over-old age couples' conditions are a main risk factor in families with stunting risk at 48.3%, and then the risk factor in the next sequence is improper lateritic ownership (29,0%), too many children (27,7%), risk factors are too close to birth distance (10.8%) and too young to become pregnant (9.7%). An unworthy risk factor of drinking water resources is the lowest risk factor at 5.2%. Assistance for families with risk of stunting through strengthening family planning programs, providing latrines and proper drinking water sources through relevant stakeholders and corporate social responsibility  partnerships is expected to reduce stunting rates in Brebes Regency.  Key words: family with stunting risk, four too aspect, latrines, sources of drinking water, stunting